Anther-Feeding-Induced RNAi in Brassicogethes aeneus Larvae - Willow, Jonathan; Soonvald, Liina; Sulg, Silva; Kaasik, Riina; Silva, Ana Isabel; Taning, Clauvis Nji Tizi; Christiaens, Olivier; Smagghe, Guy; Veromann, Eve (Frontiers in Agronomy, 2021)
The biosafety aspect of applying double-stranded RNA (dsRNA) in crop pest management is rooted in dsRNA's mode of action, which displays nucleotide sequence-specificity to a particular region of a messenger RNA (mRNA), against which the insecticidal dsRNA is designed. This prominent and promising class of insecticides therefore has the potential to target a single pest species while conferring negligible effect on non-target organisms. Recent studies examining the effect of target-specific dsRNA in adults of the pollen beetle Brassicogethes aeneus, a major pest of oilseed rape (Brassica napus) crops in Europe, suggest the potential for developing a gene-silencing approach within integrated B. aeneus management. The present study examines the efficacy of target-specific dsRNA on target-mRNA silencing, and subsequent gene-silencing-induced mortality, in B. aeneus larvae, as this life stage represents a critical target for achieving optimal integrated B. aeneus control. Treatment applications occurred via feeding on dsRNA-treated anthers for 3 d. We observed variable gene-silencing efficacy, all target treatments having a significant or marginally significant effect after 3 d of dsRNA feeding, with greater variability at 6 d. These results further validated significant gene-silencing-induced mortality observed for one of the target treatments. Moreover, gene-silencing-induced mortality occurred at a quicker rate in B. aeneus larvae compared to what has been previously observed in B. aeneus adults. Finally, we consider refinements that must be made to B. aeneus larval bioassay setups to promote and strengthen future larval studies regarding this important crop pest species.